Repeatability of corrosion parameters for titanium-molybdenum alloys in 0.9% NaCl solution - Capela, Marisa Veiga [UNESP]; Acciari, Heloisa Andréa [UNESP]; Capela, Jorge Manuel V. [UNESP]; Carvalho, Thaisa M. [UNESP]; Melin, Maria Cecilia S. [UNESP] (Elsevier B.V. Sa, 2008)
The influence of the Mo content on the corrosion resistance of Ti-Mo alloys has been investigated using electrochemical methods in 0.9% NaCl solution, which simulates the environment of the human body. In this work, commercially pure titanium (cp-Ti), Ti-6.5Mo, Ti-8.5Mo and Ti-10Mo alloys were studied. Open circuit potential (OCP) with time and potentiodynamic direct scanning (PDS) were carried out and the experimental results were analyzed using statistical methods. Regression analysis, analysis of variance (one-way ANOVA) and confidence intervals were applied to obtain the different kinetic parameters involved in the corrosion resistance for these alloys. The addition of the molybdenum to the Ti-Mo alloys increased the values of the corrosion potential, E(corr), and the polarization resistance, R(p), decreasing the oxidation tendency in the following order: cp-Ti > Ti-6.5Mo > Ti-8.5Mo > Ti-10Mo. Based on the results obtained, a sigmoidal model was proposed which describes this variation. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Titanium-molybdenum alloys; Biomaterials; Chloride corrosion; Potentiodynamic direct scanning